The Scientific Principles of Islamic Education - Mirnawati; Suarni; Saprin (South Sulawesi Education Development (SSED), 2022)
The basis of Islamic education is an operational foundation used to realize the ideal basis/source of Islamic education. The operational basis of Islamic education is of seven kinds: historical, sociological, economic, political and administrative, psychological, philosophical, and religious. The operational basis of everything is religion because religion is a frame for activities with Islamic nuances. This paper examines the principles of Islamic education as a scientific discipline. The results of the study show that the principles of Islamic education have qualified as a scientific discipline. Science must have the conditions for the existence of formal objects, research methods and systematics. Learners are human beings, meaning that the material object of Islamic education is human beings. However, man is also used to be an object by other sciences. Learners in Islamic education are explained in more detail. In the aspect of the method, the procedure for the Islamic education method is to pay attention to the factors that influence it, namely the purpose of Islamic education, students, situations, facilities, and personal educators. In the systematic aspect, the components of Islamic education include the objectives of Islamic education, the content/material of Islamic education, Islamic education methods, and evaluation. Thus, Islamic education is counted as an autonomous/stand-alone science because it has met the requirements as a science